2016
DOI: 10.1016/j.coviro.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral targets of human noroviruses

Abstract: Human noroviruses are major causative agents of sporadic and epidemic gastroenteritis both in children and adults. Currently there are no licensed therapeutic intervention measures either in terms of vaccines or drugs available for these highly contagious human pathogens. Genetic and antigenic diversity of these viruses, rapid emergence of new strains, and their ability to infect a broad population by using polymorphic histo-blood group antigens for cell attachment, pose significant challenges for the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 99 publications
(96 reference statements)
1
23
0
Order By: Relevance
“…Another study has also reported that these genes can tolerate few nucleotide changes [ 48 ]. This observation is not unexpected due to their critical functions in viral replication, viral protease and RdRP genes are highly conserved [ 40 , 49 ] and have been attractive targets for the design and development of antiviral strategies. Nucleotide diversity was also observed in regions of the p48, NTPase and VPg genes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also reported that these genes can tolerate few nucleotide changes [ 48 ]. This observation is not unexpected due to their critical functions in viral replication, viral protease and RdRP genes are highly conserved [ 40 , 49 ] and have been attractive targets for the design and development of antiviral strategies. Nucleotide diversity was also observed in regions of the p48, NTPase and VPg genes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is no therapeutic approved for the treatment of norovirus (NoV) infections, peptidomimetic inhibitors of the NoV protease (Figure 1) have emerged recently as a promising option. 1 Indeed, NoV 3C-like cysteine protease is essential to generate mature nonstructural proteins by cleavage of the viral polyprotein. Transition state inhibitors, such as compound 1 , 2 in which the peptidic moiety is selectively recognized by the 3CL protease while the electrophilic warhead reacts with Cys139 to form a covalent bond, can block the protease enzymatic activity (Figure 2).…”
mentioning
confidence: 99%
“…Closer examination of the HBGA binding site reveals that there are two subsites involved in HBGA binding. A conserved primary site (site 1), binding either the Gal residue in GI or the secretor-Fuc in GII, and a secondary evolving site (site 2) that is susceptible to sequence and structural alterations, allowing strain-specific HBGA binding [18,20,21] (Figure 2b, c). Site 2 in GII.4 variants identified post-2002 have evolved the ability to bind non-secretor Lewis HBGAs, and that might explain the prevalence of these variants [18].…”
Section: Hbga Recognition By Human Novsmentioning
confidence: 99%